Description of Knowledge and Attitudes about HIV/AIDS on Young Homosexuals in Sleman Regency Yogyakarta - Erika Nurwidiyanti; Nessy Anggun Primasari; Daryadi Daryadi (D'Nursing and Health Journal (DNHJ), 2021)
Introduction: Homosexuals community is one of the communities which have the possibility of spreading HIV/AIDS infections. According to the pilot study in a homosexual community in Sleman Regency, at least 78 people are teenagers and have a risk to be infected with HIV/AIDS. This study aimed to describe the knowledge and attitudes of young homosexuals about HIV/AIDS, and also the correlation between it in the Sleman Regency of Yogyakarta. Method: This research is descriptive-analytic. The number of samples is 30 young homosexuals with a total sampling method. Data are collected with questionnaires. Data analysis using univariate test and bivariate test with Spearman Rank correlation. Result: The results showed that knowledge about HIV/AIDS among young homosexuals is a moderate category about 56,7%, low category about 26,7%, and high category about 16,6%. The attitudes towards HIV/AIDS among the young homosexual majority is good about 43,3%, neutral attitudes about 33,3%, and worse attitudes about 23,3%. There was a significant positive correlation between knowledge of HIV/AIDS with the attitudes towards HIV/AIDS among the young homosexual in Sleman Regency indicated Spearman Rank correlation 0,541 with a p-value of 0,002. Conclusion: The knowledge about HIV/AIDS among the young homosexual majority is an average category. The attitudes towards HIV/AIDS among the young homosexual majority is good behavior. There was a correlation between knowledge and attitudes toward HIV/AIDS among young homosexuals in Sleman Regency Yogyakarta. It is important to nursing to give them health education continuously so the spreading of HIV/AIDS in teenagers can be controlled.